Respiratory and laryngeal symptoms secondary to gastro-oesophageal reflux. Issue 4 (4th May 2011) - Rafferty, G; Mainie, I; McGarvey, L P A
Abstract : Gastro-oesophageal reflux may cause a range of laryngeal and respiratory symptoms. Mechanisms responsible include the proximal migration of gastric refluxate beyond the upper oesophageal sphincter causing direct irritation of the larynx and lower airway. Alternatively, refluxate entering the distal oesophagus alone may stimulate oesophageal sensory nerves and indirectly activate airway reflexes such as cough and bronchospasm. Recognising reflux as a cause for these extraoesophageal symptoms can be difficult as many patients do not have typical oesophageal symptoms (eg, heartburn) and clinical findings on laryngoscopy are not very specific. Acid suppression remains an effective treatment in the majority of patients but there is growing appreciation of the need to consider and treat non-acid and volume reflux. New opinions about the role of existing medical and surgical (laparoscopic techniques) treatment are emerging and a number of novel anti-reflux treatments are under development.